Characteristics and Risk Factors of Children Requiring Prolonged Mechanical Ventilation vs. Non-prolonged Mechanical Ventilation in the PICU: A Prospective Single-Center Study - Yanling Liu; Yanling Liu; Yanling Liu; Qingyue Wang; Qingyue Wang; Qingyue Wang; Jun Hu; Jun Hu; Jun Hu; Fang Zhou; Fang Zhou; Fang Zhou; et al. (Frontiers Media S.A., 2022)
BackgroundProlonged mechanical ventilation (PMV) has become an enormous challenge in intensive care units (ICUs) around the world. Patients treated with PMV are generally in poor health. These patients represent a select cohort with significant morbidity, mortality, and resource utilization. The status of children who have undergone PMV in China is unknown. Our goal is to investigate the prevalence and characteristics of pediatric patients with PMV, as well as the risk factors of PMV in the pediatric intensive care unit (PICU).MethodsThe subjects were divided into two groups. The PMV group(MV ≥ 14 days) and the non-PMV group(2 days < MV <14 days). The baseline characteristics, treatments, mortality and other results between the two groups were compared. The risk factors associated with PMV were evaluated using univariate and multivariable analyses.ResultsOf the 382 children enrolled, 127 (33.2%) received prolonged mechanical ventilation. The most common cause of MV in the PMV group was acute lung disease (48.0%), followed by acute circulatory system disease (26.0%), acute neurological disease (15.0%), postoperative monitoring (10.2%), and others (0.8%). Comorbidities were more prevalent among the PMV group (P = 0.004). The patients with PMV had a higher rate of premature birth (24.4 vs. 14.1%, P = 0.013) and higher PIM3 score at admission [5.6(3.0-9.9) vs. 4.1(1.7-5.5), P < 0.001]. The use of inotropes/vasopressors (63.8 vs. 43.1%, P < 0.001) was more common in patients with PMV compared with those in the non-PMV group. In the PMV group, the rate of extubation failure (39.4 vs. 6.7%, P < 0.001) was higher than the non-PMV group. The median hospital stay [35(23.0-50.0)d vs. 20(14.0-31.0)d, P < 0.001], PICU stay [22(15.0-33.0)d vs. 9(6.0-12.0)d, P < 0.001], hospitalization costs [¥391,925(263,259-614,471) vs. ¥239,497(158,723-350,620), P < 0.001], and mortality after 1-month discharge (22.0 vs. 1.6%, P < 0.001) were higher in the PMV group. Multivariate analysis revealed that age <1 year old, a higher PIM3 score at admission, prematurity, the use of inotropes or vasopressors, extubation failure, and ventilator mode on the first day of MV were associated with PMV.ConclusionsThe incidence and mortality of PMV in pediatric patients is surprisingly high. Premature infants or patients with severe disease or extubation failure are at higher risk of PMV. Patients with PMV exhibit a greater burden with regard to medical costs than those on non-PMV. It is important to establish specialized weaning units for mechanically ventilated patients with stable conditions.